Monitoring of the absorbed dose of rates radiation in the rural areas - Vučković Biljana; Čanaćević Smilja (The University Thought: Publication in Natural Sciences, 2016)
Man is constantly exposed to radiation from the radionuclides from the environment. This study presents the results of measuring the absorbed dose rates of natural ionizing radiation in rural areas in the municipality of Štrpce, in southern part of Kosovo and Metohija. The measurements were conducted in 20 houses in two cycles: when rooms were not heated, and when they were warmed up in the same season. Ten observed houses were with basement rooms, and ten others were without basements. The absorbed dose rate of radiation was measured by Gaiger-Miller's counter DR-M3. Mean value of the measured absorbed dose rate was 1.93 µGy/h - in the first cycle and 1.47 µGy/h - in the second cycle. At the same time the values of the absorbed dose of radiation in the environmental were measured, and obtained values were 1.77 µGy/h and 1.33 µGy/h, respectively. Relations between absorbed dose in the premises and in the environment were 1.09 in first cycle, and 1.1 in the second cycle of measurements.